Seventy years of Philippine theater an annotated bibliography of critical works, 1900-1970 - Dizon, Fe S. (1972)
This is an annotated bibliography of 435 works on Philippine theater covering the period 1900-1970, which appeared in the forms of theses, manuscripts, books, newspaper/journal articles and government documents. It attempts to preserve into one unifying whole the scattered materials that have been previously published and at the same time, hopes to facilitate the future projects of the various students, researchers and authorities of Philippine drama.